Does dermatoneuro syndrome have a viral aetiology?. (1st January 2016) - Bhoyrul, B.; Mughal, A. A.; Paulus, J.; Salamat, A.; Howarth, S.
Summary: Scleromyxoedema is a rare disease characterized by a generalized papular and sclerodermoid cutaneous eruption. It is associated with fibroblast proliferation and mucin deposition in the dermis. Most patients have a monoclonal gammopathy, defined by the presence of IgG. Treatment of scleromyxoedema is challenging, but there is mounting evidence to support the use of intravenous immunoglobulin (IVIg). Individual reports of systemic complications have been described. Dermatoneuro syndrome (DNS) is a rare but sometimes fatal manifestation, which consists of a triad of fever, coma and seizures preceded by a flu‐like illness. We describe a patient with scleromyxoedema who developed DNS. Our case highlights interesting findings suggesting that DNS may have a viral aetiology. In addition, this case demonstrates a favourable response of the cutaneous features of scleromyxoedema to IVIg.